Juridical Study of Legal Status for Foreign Creditors and Ratification of Roya Letters - Cicilia Indra Jayanti; Erikson Sihotang; I Made Mulyawan Subawa (Journal Of Social Science (JoSS), 2025)
The legal status of foreign creditors in the Republic of Indonesia remains ambiguous due to unclear norms and inconsistent regulations regarding land ownership. This uncertainty is an obstacle to foreign investment and creditor relations. This study aims to clarify the legal status of foreign creditors and the process of validating roya letters, and propose a regulatory framework that can improve legal certainty. This research uses normative legal research methods, by analyzing relevant regulations, laws, and legal literature to assess the existing legal framework. The research findings show that existing legal provisions lack clear guidance for foreign creditors, especially regarding the validation of roya letters. This creates barriers to foreign investment. To improve the legal landscape, it is important for policymakers to develop concrete regulations governing the validation of roya letters for foreign legal documents. Further research is needed to explore the implications of this regulation on the rights of foreign creditors and investment in Indonesia.